CALL BROADCASTING AND AUTOMATED RECORDERS AS TOOLS FOR ANURAN SURVEYS IN A SUBARCTIC TUNDRA LANDSCAPE - Perry, Gad; Mannan, R. Nicholas; Andersen, David E.; Boal, Clint W. (Journal of North American Herpetology, 2014)
Relatively little is known about population ecology of anurans in arctic and subarctic tundra regions, in part because it is difficult to survey anurans in these landscapes. Anuran survey protocols developed for temperate regions have limited applicability in arctic and subarctic tundra landscapes, which may lack roads and vehicle access, and experience variable and inclement weather during short anuran breeding seasons. To evaluate approaches to address some of the limitations of surveying anurans in tundra landscapes, we assessed the effectiveness of using breeding call broadcasts to increase detection of Boreal Chorus Frogs (Pseudacris maculata) and Wood Frogs (Lithobates sylvaticus) near Cape Churchill, Manitoba, Canada. We also evaluated how counts of anurans derived from automated audio recorders compared with those obtained simultaneously by observers. We detected on average 0.4 additional Wood Frogs per survey when we broadcasted calls (x = 0.82, SD = 1.38), an increase of > 40% compared to surveys without broadcasts (x = 1.24, SD = 1.51; Wilcoxon test; Z = 2.73, P = 0.006). In contrast, broadcasting Boreal Chorus Frog calls did not increase the number of chorus frog detections (Wilcoxon test; Z < 0.001, P > 0.90). Detections of Wood Frogs in a 100-m radius were lower via automated recorders (x = 0.60, SD = 0.87 SD) than by observers during simultaneous surveys (x = 0.96, SD = 1.27 Z = 2.07, P = 0.038), but those of Boreal Chorus Frogs were not different (x = 1.72, SD = 1.31;x = 1.44, SD = 1.5; Z = 1.55, P > 0.121). Our results suggest that broadcasting calls can increase detection of Wood Frogs, and that automated recorders are useful in detecting both Wood Frogs and Boreal Chorus Fogs in arctic and subarctic tundra landscapes.